Chauvinistic Saying or Wise Saying: Assessing the Views on the Impact of Some Ghanaian Proverbs and Sayings on Gender Dynamics in the Frafra Traditional Area of Ghana - Cuthbert Baataar; Thomas Azagsiba Agana; Samuel Adadi Akapule (Current Progress in Arts and Social Studies Research Vol. 6, 2024)
Most cultures recognize gender differences, but the problem emerges when such differences are misunderstood as gender inequity, especially to the detriment of women. Gender disparity is evident in one component of culture, namely language, and more specifically the use of wise saying also known as proverbs. Wise saying is used interchangeably with proverbs which are said to contain a society’s wisdom. Proverbs are historic moral and wisdom statements that are passed down from generation to generation. They are an heirloom in Africa that is passed down from the generations via word of mouth. Proverbs are considered very important in the lives of indigenous peoples and play an important role in the culture of the native Africans. They serve as tools for portraying and interpreting all of Africa’s ideas and values. People’s action or inactions are frequently reflected in the meanings and interpretations of proverbs in some communities. This study investigates how wise saying or proverbs among the Frafra Traditional Area in the Upper East Region in Ghana may impact on gender relations. The Frafras are one of the Ghanaian ethnic groups who live primarily in the Sahelian Upper East Region. Using a Critical Discourse Analysis (CDA), we discovered that while some proverbs show masculine supremacy such as the construction of masculinity, ironically, exposes males to significant hazards in their attempts to meet society’s expectations. These proverbs implicitly limit the socio-cultural space in which men can communicate their socially created ordeals. This research is relevant to policymakers at the global, national and local levels including other language and culture, and stakeholders because it provides a balanced examination of how gender (in)equality is portrayed in proverbs. To address gender inequality in the Frafra traditional area in Ghana holistically, we recommend that the traditional image of men in proverbs needs to be critically re-examined. As a result, more Frafra subgroups should be included in future research to discover if their interpretations of these proverbs differ.